The Idea of Representatives of Indigenous and Tribal Peoples in the Regional Representative Council - Joesoef, Iwan Erar (Law Research Review Quarterly, 2018)
Recognition, admiration and protection of Indigenous Peoples Rights has been adopted both under global dimension such as international convention and national dimension such as Indonesian Constitution and Indonesian National Positive Law. Notwithstanding that Recognition, admiration and protection of Indigenous Peoples Rights has been adopted both under global and national dimension, there are still many legal conflict upon land rights that is some legal problem arise from transferring of Ã¢â‚¬Å“Tanah UlayatÃ¢â‚¬Â (Ancestral Lands) to Government, Private Sector or Individual of which give the disadvantage to MHA. The main problem is difference perception among institutions (Executive, Judicative and Legislative) in their consistency upon giving the compensation concerning to transferring Ã¢â‚¬Å“Tanah UlayatÃ¢â‚¬Â (Ancestral Lands) of which causing re-claim upon such Ã¢â‚¬Å“Tanah UlayatÃ¢â‚¬Â (Ancestral Lands), there are no basis of multi dimension approach (anthropology, sociology and others discipline including legal discipline). It means that the legal formal approach only cannot give the effective result. The legal questions are, could MHA constitutionally have a representative inside the Province Parliament and how about the type of Democracy which appropriate and able to submit their aspiration. This conceptual article will elaborate how to make a representative of MHA inside the Province Parliament by combining the value of individual and collective interest in equilibrium in one harmony of democracy as Hegel (1770-1831) opinion that dualism between individual and collective interest under democracy should be omitted by formulating the conception of State. Under this equilibrium the performance of democracy will be optimized.